2011
DOI: 10.4048/jbc.2011.14.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Characteristics Influencing Non-Sentinel Lymph Node Involvement in Clinically Node Negative Patients with Breast Cancer

Abstract: PurposeThe negative sentinel lymph node (SLN) biopsy avoids conventional axillary dissection in patients with breast cancer with clinically negative axilla. Despite negative SLN, there is a risk of leaving involved non-SLN behind in the axilla. We investigated the predictive power of tumor characteristics for non-SLN metastasis.MethodsLymphatic mapping with blue dye method for SLN biopsy and level 1-2 axillary dissections were performed to establish axillary status in 59 patients with T1 and T2 breast cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
5
0
2
Order By: Relevance
“…The univariate analysis performed in this study illustrated that the HR status, HER2 status, Ki67 level, clinical node stage, clinical T stage, breast pCR, and the number of sentinel metastases were associated with nonsentinel metastasis, consistent with earlier clinical studies 5,20,21 . Lymphovascular invasion was associated with NSLN metastasis, consistent with most other studies 22,23 . In addition, some studies have shown that the molecular subtype classification of BC is a powerful predictor of NSLN metastasis and that some subtypes are more likely to have NSLN metastases than others; however, no similar conclusions have been reached here 30,31 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The univariate analysis performed in this study illustrated that the HR status, HER2 status, Ki67 level, clinical node stage, clinical T stage, breast pCR, and the number of sentinel metastases were associated with nonsentinel metastasis, consistent with earlier clinical studies 5,20,21 . Lymphovascular invasion was associated with NSLN metastasis, consistent with most other studies 22,23 . In addition, some studies have shown that the molecular subtype classification of BC is a powerful predictor of NSLN metastasis and that some subtypes are more likely to have NSLN metastases than others; however, no similar conclusions have been reached here 30,31 .…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the axillary lymph node‐negative rate after NAC was 50.8%. Previous reports on axillary lymph node‐positive patients showed a conversion rate of axillary nodal status after NAC of 40% to 75% 20‐23 . Thus, a considerable number of patients can theoretically avoid ALND.…”
Section: Discussionmentioning
confidence: 96%
“…Axillary metastasis was significantly associated with LVI (p<0.001). 9 Nomogram score were assigned to all patients based on criteria specified in Memorial Sloan Kettering Cancer nomogram.…”
Section: Review Of Literature Factors Affecting Involvement Of Axillamentioning
confidence: 99%
“…One of the most suitable factors notably evaluated by the researchers is lymphovascular invasion. Up to now, a great number of studies have been conducted in order to find the prognostic role of lymphovascular invasion in breast cancer, especially in 5768 node negative patients (Sebastian et al, 2004;Pauline et al, 2005;Gurleyik et al, 2011). It seems that this factor may be an adverse prognostic factor for survival in patients with breast cancer, especially those with the node negative disease.…”
Section: Vascular Invasion As An Independent Prognostic Factor In Lymmentioning
confidence: 99%